Assessing Digital Attitude Competence of Prospective Chemistry Teacher in Indonesia: A Case of Lampung Univesity - Saputra, Andrian (Jurnal Pendidikan Progresif, 2021)
Assessing Digital Attitude Competence of Prospective Chemistry Teacher in Indonesia: A Case of Lampung Univesity. Objective: This study aims to analyze the competence of digital attitudes of chemistry teacher candidates at the University of Lampung. Methods: A total of 200 chemistry teacher candidate students at the teacher training faculty, Universitas Lampung were randomly selected as research samples. The data obtained were analyzed using exploratory factor analysis techniques, reliability, correlation, average value, and variance. Findings: Analysis shows that the questionnaire items are grouped into five main factors with the Cronbach alpha coefficient and the percentage of variance as follows: attitudes towards digital content creation (α = 0.919; s2 = 39.546%); attitudes towards digital information (α = 0.885; s2 = 7.806%); attitudes towards digital security (α = 0.871; s2 = 4.321%); attitudes towards digital problem solving (α = 0.755; s2 = 3.410%); and attitudes towards digital information (α = 0.793; s2 = 2.974%). Conclusion: The comparison of the mean and grand mean values shows that attitudes towards information and digital security are more dominant factors in how chemistry teacher students respond to digital devices that support learning.Keywords: digital attitude competence, chemistry teacher candidates, factor analysis. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202108